Association between Asian Dust-Borne Air Pollutants and Daily Symptoms on Healthy Subjects: A Web-Based Pilot Study in Yonago, Japan - Majbauddin, Abir (J Environ Public Health, 2016)
During the spring, Asian dust (AD) repeatedly makes its way to Japan, originating from drylands. We evaluated the association between AD-borne air pollutants and daily reported subjective symptoms in healthy subjects. We constructed an Internet questionnaire on daily ocular, nasal, respiratory, and skin symptoms. Forty-two healthy volunteers residents of Yonago (mean age, 33.57) were selected from the self-reporting web-based survey and recorded their symptoms between 1 and 31 of March 2013. We also collected information on levels of suspended particulate matter (SPM), particulate matter < 2.5 µm (PM(2.5)), sulfur dioxide (SO(2)), and nitrogen oxide (NO(x)) per hour on each of those days. SPM and PM(2.5) were the dominant pollutants recorded throughout the month. A positive correlation was observed between SPM and ocular (r = 0.475, p < 0.01), nasal (r = 0.614, p < 0.001), and skin (r = 0.445, p < 0.05) symptoms. PM(2.5) correlations were significant for ocular (r = 0.428, p < 0.05), nasal (r = 0.560, p < 0.01), and skin (r = 0.437, p < 0.05) symptoms. Our findings provide introductory evidence of AD-borne air pollutants and their association with several bodily symptoms in healthy subjects with the implementation of a self-administrated web-based survey application.